The Effects of Curcumin on Diabetes Mellitus: A Systematic Review - Marton, Ledyane Taynara; Pescinini-e-Salzedas, Laís Maria; Camargo, Maria Eduarda Côrtes; Barbalho, Sandra M.; Haber, Jesselina F. dos Santos; Sinatora, Renata Vargas; Detregiachi, Claudia Rucco Penteado; Girio, Raul J. S.; Buchaim, Daniela Vieira; Cincotto dos Santos Bueno, Patricia (Frontiers in Endocrinology, 2021)
Diabetes mellitus (DM) is an ensemble of metabolic conditions that have reached pandemic propotions worldwide. Pathology's multifactorial nature makes patient management, including lifelong drug therapy and lifestyle modification, extremely challenging. Currently, there is growing evidence about the effectiveness of using herbal supplements in preventing and controlling DM. Curcumin is a bioactive component found Curcuma longa, which exhibits several physiological and pharmacological properties such as antioxidant, anti-inflammatory, anticancer, neuroprotective, and anti-diabetic activities. For these reasons, our objective is to systematically review the effects of Curcuma longa or curcumin on DM. Databases such as PUMED and EMBASE were searched, and the final selection included sixteen studies that fulfilled the inclusion criteria. The results showed that curcumin's anti-diabetic activity might be due to its capacity to suppress oxidative stress and inflammatory process. Also, it significantly reduces fasting blood glucose, glycated hemoglobin, and body mass index. Nanocurcumin is also associated with a significant reduction in triglycerides, VLDL-c, total cholesterol, LDL-c, HDL-c, serum C Reactive Protein, and plasma malonaldehyde. Therefore, it can be considered in the therapeutic approach of patients with DM.